2015
DOI: 10.1007/s00203-015-1089-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gut microbiota of healthy children from two different geographic regions of Thailand

Abstract: In Thailand, food consumption by people from each region is different. This can be an important environmental factor which shapes the gut microbiota further affecting their health. This study aimed to use quantitative PCR (qPCR) to investigate the intestinal microbial community in 60 healthy children (aged 8-11 years) living in specific areas, namely central (CT) and northeastern (NE) Thailand where each region has its own typical food consumption. The children from NE had significantly higher consumption freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 60 publications
2
38
0
1
Order By: Relevance
“…Host parameters such as age, gender, and body mass index (BMI) are reported to be linked to the composition of the gut microbiota [7–11], and differences in dietary habits have been shown to affect the bacterial diversity of the human gut microbiota. Together, these results partially explain why differences in the composition of the gut microbiota are observed in persons residing in different geographical regions [6, 12–14]. …”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Host parameters such as age, gender, and body mass index (BMI) are reported to be linked to the composition of the gut microbiota [7–11], and differences in dietary habits have been shown to affect the bacterial diversity of the human gut microbiota. Together, these results partially explain why differences in the composition of the gut microbiota are observed in persons residing in different geographical regions [6, 12–14]. …”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, differences were found for the abundances of only six bacterial families between only two of the seven regions (Table 2 and Additional file 1: Table S5), suggesting that area of residence does not strongly affect the composition of the fecal microbiota in the healthy adults living in Japan. Therefore, the dietary habits and daily routines that are common in the various regions of Japan today (Additional file 1: Table S9) are not sufficiently distinct as to lead to clear microbial diversity in the gut, which is in contrast to the current situation in Thailand [14] and Mongolia [10]. …”
Section: Discussionmentioning
confidence: 99%
“…31 Diet is considered a trigger of intestinal microbiota diversity by altering the gut microenvironment. [32][33][34][35] Recently, we reported that gut microbiota, particularly the phylum Firmicutes and a high fat diet increases the chance of developing obesity. 11 This observation is in agreement with our data (table II), where the medium and high tertiles of Firmicutes RA were statistically associated with obesity, suggesting that the amount of Firmicutes RA is important to get a state of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, diet patterns differ geographically in the same country [21]. Also, a number of dissimilarities in dietary patterns were reported between island and inland areas of South Korea [22].…”
Section: Discussionmentioning
confidence: 99%